PERILAKU PEDAGANG PASAR TRADISIONAL SAMBONGGEDE KECAMATAN MERAKURAK KABUPATEN TUBAN DALAM MEMPERTAHANKAN EKONOMI RUMAH TANGGA PASCA COVID-19 - Fernandez, Frederik (Universitas Wijaya Kusuma Surabaya, 2023)
This study aims to determine the behavior of traditional market traders in Sambonggede Village, Merakurak District, Tuban Regency, East Java when the Covid-19 pandemic occurred. This study uses a type of qualitative research. Data collection techniques were carried out by observation, interviews and documentation. The informants in this study were traditional market traders in Sambonggede Village, Merakurak District, Tuban Regency, totaling 6 people as research objects. The research results obtained were that during the Covid-19 pandemic, the existence of traditional markets greatly affected the income of traditional market traders, which was marked by a very drastic reduction in income. The traders still maintain the quality of production, because it is a basic daily need. In addition to maintaining production quality, traders also use certain strategies to maintain existing networks by establishing personal relationships with customers. As for determining the price, traditional market traders use a bargaining system and an agreement between the seller and the buyer. During a pandemic, to improve product quality, traditional market traders sort goods taken from raw material producers in order to avoid product damage. Meanwhile, in improving the quality of service, traditional market traders serve buyers one by one, by providing products at home in that way, buyers can also ask directly about the availability of the product to be purchased. Keywords: trader behavior, traditional markets, the Covid-19 pandemic.